2010
DOI: 10.5194/acp-10-3965-2010
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas relationships in the Indian summer monsoon plume measured by the CARIBIC passenger aircraft

Abstract: Abstract. During the Indian summer monsoon period 2008, regular measurement flights were performed by the CARIBIC aircraft between Germany and India. Measurements included whole air sampling and subsequent analysis for greenhouse gases (CH 4 , CO 2 , N 2 O, SF 6 ) and in-situ measurements of CO, O 3 , and H 2 O. For all these tracers a distinct monsoon signature was observed in the longitude range 50-80 • E south of 40 • N at flight altitudes 8-12.5 km. The formation of a monsoon plume with enhanced mixing rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 64 publications
7
97
2
Order By: Relevance
“…We use in situ measurements made from April until December 2008 made during flights from Frankfurt, Germany (50.0 • N, 8.5 • E) to Chennai, India (13.0 • N, 80.2 • E). The flights to and from Chennai take similar routes to those shown in Schuck et al (2010), providing a monthly snapshot of the distribution of NO y at the cruise altitude of 10-12 km throughout a large fraction of the year. The uncertainty associated with the CARIBIC NO y measurements is ∼ 8 % for mixing ratios around 450 ppt.…”
Section: Observational Data Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…We use in situ measurements made from April until December 2008 made during flights from Frankfurt, Germany (50.0 • N, 8.5 • E) to Chennai, India (13.0 • N, 80.2 • E). The flights to and from Chennai take similar routes to those shown in Schuck et al (2010), providing a monthly snapshot of the distribution of NO y at the cruise altitude of 10-12 km throughout a large fraction of the year. The uncertainty associated with the CARIBIC NO y measurements is ∼ 8 % for mixing ratios around 450 ppt.…”
Section: Observational Data Setsmentioning
confidence: 99%
“…Examining the seasonal trend in the observations shows that between 15-25 • N there is a maximum in NO y mixing ratios towards the start of the year, which generally decreases by ∼ 30-50 % towards December. Previous studies have shown that emissions directly below the flight path have an impact on composition of the UT over India (Schuck et al, 2010). This reduction in NO y through the year may be partially explained by the occurrence of the Indian monsoon, where a larger fraction of NO y is lost via wet deposition, but also by the change in the location of the tropopause.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Model and satellite data consistently localised high mixing ratios of CH 4 between 60 • E and 120 • E around 30 • N, a region included in our extended South Asian region (Table 2) at and above cruising altitude, at pressure altitudes between 300 and 100 hPa (Park et al, 2004;Xiong et al, 2009). Schuck et al (2010) showed that air masses sampled north of 30 • N generally travel for more than a week, in contrast with air masses south of 30 • N which had ground contact within the last four days prior to sampling. Baker et al (2011) confirmed that in the southern monsoon region, sampled air masses travelled 3 to 6 days before sampling, and 9 to 12 days in northern monsoon region.…”
Section: Two Contrasted Transport Conditions: Rapid Uplifting Of Pollmentioning
confidence: 99%
“…Most of these measurements are made at weekly or fortnightly time intervals. Two aircraft-based measurement programmes, namely, Civil Aircraft for the regular Investigation of the atmosphere Based on an Instrument Container (CARIBIC) (Brenninkmeijer et al, 2007) and Comprehensive Observation Network for TRace gases by AIrLiner (CONTRAIL) (Machida et al, 2008) have provided an important first look at the southern Asian CO 2 budget, but these data have their own limitations (Patra et al, 2011;Schuck et al, 2010Schuck et al, , 2012. It is pertinent to mention here that until now, there have been no reports of CO 2 measurements over an urban location in India.…”
mentioning
confidence: 99%